(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
This study aims to examine the potential of adopting circular economy principles in the Indian Fashion and Textile industry and its feasibility through the adoption of lean manufacturing practices, with the objective of achieving an “Atmanirbhar Bharat” goal. The research utilizes a mixed-method approach, incorporating discussions on the need of circularity and the potential way a head to achieve it through Lean Manufacturing Technique and case discussion. The study investigates the potential correlation between lean manufacturing, which emphasizes waste reduction and operational efficiency in manufacturing processes, and the circular economy concept,which revolves around minimizing waste, reducing resource consumption,and promoting reuse and recycling. Circular economy strives to establish a closed-loop system,instead of the existing Linear Economic System. Through Lean Systems, the materials and products are utilized for as long as possible, aiming to eliminate wastage. The Textile & Apparel industry ranks as the second most polluting sector globally, contributing to environmental degradation, social injustice, and economic instability.